GABA Enhancement of Maternal Defense in Mice: Possible Neural Correlates - Lee, Grace (2007)
Previous studies have shown that low doses of GABA(A) receptor agonists facilitate maternal defense of offspring (maternal aggression), without significantly affecting other maternal behaviors. In addition, it has been demonstrated that endogenous changes in GABAergic neurotransmission occur in association with lactation. This study investigated the effects of GABA(A) receptor agonist, chlordiazepoxide (CDP), a benzodiazepine (BDZ), on maternal behaviors including aggression, and identified brain regions with altered activity in association with treatment. Another aim of the study was to determine whether CDP injections could prevent decreases in maternal aggression that occur with pup separation. Intraperitoneal injections of 1mg/kg of CDP significantly increased maternal defense without affecting other maternal behaviors, although a trend towards elevated nursing was noted. CDP significantly reduced c-Fos in lateral septum (LS) and caudal periaqueductal gray (cPAG) in behaviorally-experienced mice relative to vehicle-injected controls. In behaviorally-naïve subjects, CDP also decreased c-Fos in LS, but in cPAG this decrease was just above significance (p = 0.051). CDP was not sufficient to “rescue” maternal aggression when pup stimulus was removed. Overall, these studies provide further insights into the role for GABA in maternal behaviors, including aggression, and how and where BDZs may act to modulate behavior.